Penerapan Metode Waterfall dalam Pengembangan Aplikasi Edukasi Pelestarian Mangrove Berbasis Mobile - Hermansyah, Hermansyah; Wijaya, Rian Farta; Wahyuni, Sri; Putra, Agil Dwi (Universitas Harapan Medan, 2024)
The mangrove ecosystem plays a vital role in maintaining coastal environmental balance. However, mangrove degradation continues to increase due to a lack of public awareness and education about its benefits and conservation methods. This study aims to develop a mobile-based educational application focused on introducing mangroves, highlighting their benefits, and demonstrating conservation techniques. The Waterfall method was applied in its development, consisting of the stages of requirements analysis, design, implementation, testing, and maintenance. This method was chosen for its structured and systematic approach, allowing for a well-planned application development that meets user needs. Testing results indicate that this application provides educational information interactively and is easily accessible to a broad audience, especially students and coastal communities. This application is expected to raise public awareness of the importance of mangrove conservation and serve as an effective solution in disseminating information about the mangrove ecosystem